2002
DOI: 10.1034/j.1600-0447.2002.201249.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion from submucosal salivary glands of the ferret in response to a cholinesterase inhibitor applied onto the oral mucosa

Abstract: Parasympathomimetics or cholinesterase inhibitors taken orally may relieve dry-mouth symptoms, but this route of administration is often associated with adverse systemic reactions. In the present study, an animal model was worked out aimed at stimulating the submucosal glands and avoiding systemic effects. In the anesthetized ferret, saliva from the parotid, sublingual and submandibular glands was prevented from reaching the mouth. Vehicle or physostigmine was applied topically for 10 min on the buccal and lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, a certain contribution by the major glands to the volume of saliva cannot be excluded and in fact seems likely at the dose levels of physostigmine associated with systemic cholinergic adverse effects. This idea gains support from our previous animal studies, where the buccal mucosa was exposed to increasing concentrations of physostigmine and the ducts of the major glands were cannulated to detect any systemically elicited flow of saliva (7).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, a certain contribution by the major glands to the volume of saliva cannot be excluded and in fact seems likely at the dose levels of physostigmine associated with systemic cholinergic adverse effects. This idea gains support from our previous animal studies, where the buccal mucosa was exposed to increasing concentrations of physostigmine and the ducts of the major glands were cannulated to detect any systemically elicited flow of saliva (7).…”
Section: Discussionmentioning
confidence: 69%
“…Animal studies have revealed that the reversible cholinesterase inhibitor physostigmine, applied locally to the oral mucosa, causes secretion from cholinergically innervated submucosal glands (7, 8). Physostigmine, a tertiary amine, transverses the mucosal layer and prevents the degradation of acetylcholine, released from the intraglandular cholinergic nerve endings, thus enhancing the cholinergic tone of the secretory cells (7, 8).…”
mentioning
confidence: 99%
“…It has been shown that following topical application to the oral mucosa, the acetylcholinesterase inhibitor physostigmine will diffuse through the epithelium to stimulate indirectly underlying minor salivary glands, by preventing the breakdown of acetylcholine released from parasympathetic nerve endings. This alleviates symptoms of xerostomia for 2–3 h without producing systemic effects (Hedner et al , ; Ekström & Helander, ; Khosravani et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…As judged from the acute salivatory effect of amisulpride currently found, it is tempting to suggest that amisulpride or a molecule related to amisulpride may be developed into a ‘salivation enhancer drug’ to treat dry mouth. A drug of this kind could be applied topically to the oral mucosa with the aim of acting locally on the underlying mucosal mucin‐producing minor salivary glands under cholinergic nerve influence, as is the case for the acetylcholinesterase drug physostigmine (Ekström and Helander, 2002; Khosravani et al , 2009).…”
Section: Discussionmentioning
confidence: 99%